Investigation of toxic elements in Carassius gibelio and Sinanodonta woodiana and its health risk to humans - Arumugam, A.; Li, J.; Krishnamurthy, P.; Jia, Z.X.; Leng, Z.; Ramasamy, Nagarajan; Du, D. (SPRINGER HEIDELBERG, 2020)
Increasing toxic metal content in aquatic products has become a universal burden due to the risks to aquatic organisms and human health associated with the consumption of these products. In this study, toxic metal distribution and accumulation in the organs of fish and bivalve species of economic and culinary importance from the lower reaches of the Yangtze River are examined, and the corresponding health risks are also investigated. In general, the viscera and gill show higher concentration of metals than other tissues. The order of the accumulation sequence of metals in muscle tissue of fish and bivalve is Zn > Cu > Mn > Cr > As > Hg > Pb > Cd and Mn > Zn > Cu > As > Cr > Pb > Cd > Hg respectively. Maximum accumulation of Mn (507.50 μg g−1) and Pb (0.51 μg g−1) in the gill tissues indicates the major uptake of these metals from the water column. According to the Hazard Index (HI) calculations (based on USEPA), the analyzed metals will not cause any harmful health effects to individuals for both normal and habitual fish consumers, except for Hg and As in habitual consumers, if these species are consumed at a larger amount. Compared to the Chinese Food Health Criterion and other international standards (WHO/FAO), metal concentrations in the edible muscle tissues of the studied species are lesser than the acceptable levels and found to be fit for human consumption.